Perceived stress in adolescence and labour market participation in young adulthood - a prospective cohort study - Trine Nøhr Winding; Mette Lykke Nielsen; Regine Grytnes (BMC, 2023)
Abstract Background Adolescence is a key-developmental stage for physical, neurological, psychological, and social changes. In this developmental stage, a large number of people struggle with mental health problems like stress, anxiety, or depression. Psychological vulnerability in adolescence has previously been found to be negatively related to future low labour market participation. However, studies are lacking that investigate the impact of stress during adolescence on labour market participation in early adulthood using register data. The aim of this prospective study was therefore to examine the association between perceived stress during adolescence and labour market participation in young men and women in early adulthood. Methods A Danish cohort of 3038 participants born in 1989 was followed with use of questionnaires from age 15 to age 28. The exposure, self-reported perceived stress, was collected by questionnaires at ages 15, 18, and 21. The outcome, labour market participation, was based on register information on social benefits, such as unemployment benefits, sickness benefits, and disability benefits, collected on a weekly basis during a 4-year period. Information about the socioeconomic confounders was also gleaned from registers. Results The study found consistent associations between perceived stress from age 15 to age 21 and low labour market participation from age 25 to age 29 in both women and men after adjusting for mental health and socioeconomic confounders. The strongest associations between perceived stress and low labour market participation were seen among men who reported stress several times during adolescence. Conclusions The results indicate that although, women in general, reported being more stressed than men during adolescence and had lower labour market participation in early adulthood, there was a small group of men who had experienced stress during adolescence who were at particularly high risk of being marginalised in the labour market.